As tecnologias da informação e comunicação na perspectiva de professores do ensino médio das escolas estaduais do município de Colombo - Paraná - Silva, Elio Da (2018)
Currently, we live in a scenario where Information and Communication Technologies (ICT) are increasingly present in social and educational environments. ICTs can provide changes in the teaching-learning process, but the teacher and the school via managers and pedagogical team need to understand the potential they offer as a pedagogical resource in education. The objective of the study was to analyze the conception of teachers of the state schools of the city of Colombo-PR, on the use of ICT as a pedagogical resource in the teaching-learning process. The literature review addresses concepts and issues inherent to technology and education: technology from the perspective of studies in Science, Technology and Society (CTS) and the philosophy of technology with critical theory; ICT in education; the Paraná Digital Program (PRD) and the public policies of insertion of technologies in the state schools of Paraná; the appropriation of ICT by teachers, involving how teachers learn to use ICT, the importance of training, the incentives offered by schools through the use of ICT managers; the use of ICT by teachers for mediation of the teachinglearning process. The research was qualitative of an interpretive nature. The study was carried out in state schools in the municipality of Colombo-PR - Regional Nucleus, North Metropolitan Area. The technique for data collection was the semistructured individual interview. The study participants were 12 teachers from the disciplines of the high school curriculum matrix. The sample was intentional by criteria. The main results of the study were: teachers find difficulties for the use of ICT as; lack of infrastructure and maintenance of technological equipment in schools; lack of knowledge about how to use ICT as a pedagogical resource. Teachers use ICT by maintaining traditional methodologies with new tools. In relation to the search for knowledge on how to integrate ICT in classes and activities, the lack of initial and continuous training leads to the predominance of individuality of teachers without the guidance of managers and the maintainer. There is a lack of incentives for managers and pedagogical staff in schools for the appropriation and integration of ICT in pedagogical activities and the development of collaborative activities; the teachers have a naive conception about the ICT because they consider that the simple access to the technological tools innovates the teaching-learning process.